Levosimendan as Treatment Option in Severe Verapamil Intoxication: A Case Report and Review of the Literature. (27th July 2010) - Osthoff, Mirjam; Bernsmeier, Christine; Marsch, Stephan C.; Hunziker, Patrick R.
Abstract : Cardiovascular shock due to verapamil intoxication is often refractory to standard resuscitation methods. Recommended therapy includes prevention of further absorption of the drug, inotropic therapy, calcium gluconate, and hyperinsulinemia/euglycemia therapy. Often further measures are needed such as ventricular pacing or mechanical circulatory support. Still, mortality remains high. Levosimendan, an inotropic agent, that enhances myofilament response to calcium, increases myocardial contraction and could therefore be beneficial in verapamil intoxication. Here, we report the case of a 60-year-old patient with clinically severe verapamil poisoning who presented with shock, bradycardia, and sopor. Standard therapy including high-dose inotropes failed to ameliorate the signs of intoxication. But additional therapy with levosimendan led to rapid improvement. Based on this observation, the literature is reviewed focusing on utilization of levosimendan in the treatment of calcium channel blocker overdose. We suggest to consider levosimendan as additional treatment option in patients with cardiovascular shock due to verapamil intoxication that are refractory to standard management.